Wijsman Deferred Statistical Convergence and Wijsman Strong Deferred Cesaro Convergence of Order a of Sequences of Sets - Yilmazer, M. Cagri; Et, Mikail; Kandemir, Hacer Sengul (Amer Inst Physics, 2021)
The main purpose of this paper is to introduce the concepts of Wijsman deferred statistical convergence of order alpha and Wijsman strong deferred Cesaro convergence of order a for sequences of sets.
4th International Conference of Mathematical Sciences (ICMS) -- JUN 17-21, 2020 -- Maltepe Univ, ELECTR NETWORK
Keywords: Deferred density; deferred Cesaro mean; statistical convergence; Wijsman convergence